Prognostic significance of perioperative circulating CD56bright NK cell and recovery of NK cell activity in patients with colorectal cancer undergoing radical surgery - Jeng-Fu You; Cheng-Chi Lee; Yun-Shien Lee; Yih-Jong Chern; Chun-Kai Liao; Hung-Chih Hsu (Translational Oncology)
Introduction: Natural killer (NK) cell activity (NKA) is downregulated in patients with colorectal cancer (CRC), and its dysfunction is possibly associated with increased risk of recurrence. However, its role in prognosis of CRC remains unclear. Prior research has shown that surgical stress can suppress NKA. This study explores the relationship between NK cell/NKA and clinicopathological factors during the perioperative period in patients with CRC. Methods: We prospectively enrolled 45 patients with CRC. Venous blood samples were collected preoperatively and on postoperative day 3 (POD3) and 30 (POD30). NKA was assessed by measuring the plasma levels of NK cell-secreted IFN-γ. Results: NKA was significantly reduced on POD3 compared with baseline levels before surgery but showed significant recovery by POD30. NKA on POD30 was considerably higher in patients with advanced disease stages or one or more high-risk preoperative factors. Additionally, a higher NKA recovery in patients with advanced stage exhibited improved recurrence-free survival (RFS) and progression-free survival (PFS) (hazards ratio (HR): 0.2442). Furthermore, an increased percentage of CD56bright NK cells and a higher CD56bright/CD56dim NK cell ratio postoperatively on POD30 were associated with better RFS/PFS (HR: 0.2732, P = 0.0433 and HR: 0.2193, P = 0.024, respectively). Conclusions: Our findings indicate that a notable postoperative increase in CD56bright NK cells on POD30, both in percentage and ratio, correlates with a more favorable prognosis in CRC patients. Additionally, higher recovery rates of NKA in patients with advanced stages may offer potential applications in risk stratification and the development of treatment strategies for CRC.